Influence of anomalous low-level circulation on the Kuroshio in the Luzon Strait during ENSO. (March 2021) - Kuo, Yi-Chun; Tseng, Yu-Heng
Abstract: Basin-scale wind curl anomalies in the North Pacific associated with El Niño increase westward Kuroshio transport in the Luzon Strait, whereas those associated with La Niña reduce it. However, the Kuroshio current in the Luzon Strait is further affected by mesoscale eddies and local wind stress. Numerical experiments are conducted to demonstrate that the anomalous low-level circulation over the Philippine sea during El Niño weakens the northeasterly monsoon and favors the development of mesoscale eddies at the same time. This is caused by the increased baroclinic instability in the Subtropical Countercurrent (STCC)/North Equatorial Current region. Our results are supported by the long-term observational data. Consequently, the Kuroshio pattern in the Luzon Strait during El Niño tends to be more unsteady. During La Niña, the Kuroshio loop is enhanced in response to strengthened northeasterly winds. Furthermore, vorticity stretching, caused by local wind stress and associated curl anomalies during La Niña, contributes to the formation of a cyclonic eddy off the southeastern Taiwan. Highlights: Sensibility experiments are used to show the effects of regional wind anomalies. The anomalous wind increases baroclinic instability to the east of Luzon. The results are supported by the long-term observational data.